Phytochemical component and toxicological evaluation of purple sweet potato leaf extract in male Sprague–Dawley rats - Hisamuddin, Ahmad Safiyyu’d-din Bin; Naomi, Ruth; Bin Manan, Khairul Aiman; Bahari, Hasnah; Yazid, Muhammad Dain; Othman, Fezah; Embong, Hashim; Hadizah Jumidil, Siti; Hussain, Mohd Khairi; Zakaria, Zainul Amiruddin (Frontiers in Pharmacology, 2023)
The objective of this study is to access the toxicity of lutein rich purple sweet potato leaves (PSPL) extract in male Sprague Dawley rats. Methods and study design: 54 adult male SD rats were used. For acute toxicity study (n = 3), rats were divided into acute control and fed with 2000 mg/kg of PSPL for 14 days while for subacute toxicity study (n = 6) rats were divided into 4 groups; where rats were fed with 50, 250, 500, 1000 mg/kg for 28 days and observed further 14 days without treatment in subacute control, and subacute satellite group. Changes in body weight, blood biochemistry, haematological parameters, relative organ weight (ROW) and histological section of heart, kidney, liver, pancreas, aorta, and retina were observed for toxicity sign. Results: Gradual increase of weekly body weight, and normal level full blood count, and normal liver and kidney profile, relative organ weight, and histological sections of all stained organ tissue in treated group in comparison with the acute, subacute, and satellite control groups shows absence of signs of toxicity. Conclusion: Lutein rich PSPL extract shows no signs of toxicity up to 2000 mg/kg/day.